Activation of group II metabotropic glutamate receptors blocks zinc release from hippocampal mossy fibers - Matias, Carlos M (Biol Res, 2014)
BACKGROUND: The hippocampal CA3 area contains large amounts of vesicular zinc in the mossy fiber terminals which is released during synaptic activity, depending on presynaptic calcium. Another characteristic of these synapses is the presynaptic localization of high concentrations of group II metabotropic glutamate receptors, specifically activated by DCG-IV. Previous work has shown that DCG-IV affects only mossy fiber-evoked responses but not the signals from associational-commissural afferents, blocking mossy fiber synaptic transmission. Since zinc is released from mossy fibers even for single stimuli and it is generally assumed to be co-released with glutamate, the aim of the work was to investigate the effect of DCG-IV on mossy fiber zinc signals. RESULTS: Studies were performed using the membrane-permeant fluorescent zinc probe TSQ, and indicate that DCG-IV almost completely abolishes mossy fiber zinc changes as it does with synaptic transmission. CONCLUSIONS: Zinc signaling is regulated by the activation of type II metabotropic receptors, as it has been previously shown for glutamate, further supporting the corelease of glutamate and zinc from mossy fibers.